Speaking of Women? Exploring Violence against Women through Political Discourses: A Case Study of Headscarf Debates in Turkey - Hulya Arik (e-cadernos ces)
This paper explores the production of violence against women through political discourses in Turkey. Since the foundation of the Republic (1923), women’s bodies have been on the agenda as the markers of secular Turkish modernity. With the rise of political Islam as of the 1970s, the image of the headscarved woman has challenged the construction of “modern Republican woman” and the association of women’s bodies with secularism. Especially after the 1980s with the introduction of bans, “the headscarf issue” has intensified and become the embodiment of the clash between political Islam and the official secularist ideology. By drawing on the sexualizing aspects of the headscarf and its significance in the construction of female honour, I will demonstrate how women’s bodies are turned into readily available topics for consumption in politics. I argue that headscarf debates have factored into patriarchal discourses, which inflict violence on women on both discursive and material levels. By analysing a few cases on media reflections and art projects on the “headscarf debate”, I aim to show how women’s bodies become vulnerable to violence through political discourses.